The Effectiveness of the Merit System in Position Mutations in Human Resources and Employment Agency in Padang Panjang City, West Sumatera - Indra Aprilzoni; Februarti Trimurni (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
Work rotation or rotation is done to avoid the saturation of employees or employees on work routines that are sometimes boring and have other objective functions so that someone can master and explore other jobs in different fields in an organization. Which has a good impact on the professionalism of work and the implementation of organizational goals. For this reason, the government carries out various kinds of business. One way that the government does is by doing how the effectiveness of mutations in improving work quality. then the government expects mutations to be more optimal and achieve predetermined targets. The purpose of this research is to find out how the effectiveness of the Merit system in the position of position in the Personnel Agency and Human Resources Work in Padang Panjang City, West Sumatra Province. This research uses descriptive research method with a qualitative approach. Data collection techniques are carried out by means of interviews, observations and documentation relating to the merit system in job mutations. The data obtained were then analyzed qualitatively by reviewing all data collected, supported by interviews with a theoretical approach proposed by Tangkilisan that organizational effectiveness was measured through Targeting, Adaptation, Satisfaction, Responsibility. Through this research it can be seen that the effectiveness of the merit system in job mutations increases work optimization in an organization. However, there are some things that need to be improved, namely the achievement of targets in providing land and building tax payment services, the quality generated in carrying out mutations, and satisfaction on each performance performed.